Recruitment strategies for sarcopenia trials: lessons from the LACE randomized controlled trial - Miles D. Witham (JCSM Rapid Communications, 2021)
Abstract Background Sarcopenia is rarely diagnosed and is not recorded electronically in routine clinical care, posing challenges to trial recruitment. We describe the performance of four components of a strategy to efficiently recruit participants with sarcopenia to a trial of perindopril and/or leucine for sarcopenia: primary care vs. hospital recruitment, a comparison of central vs. local telephone pre‐screening, performance of a questionnaire on physical function conducted as part of the pre‐screening telephone call, and performance of bioimpedance measurement to identify low muscle mass. Methods Hospital‐based recruitment took place through inpatient and outpatient geriatric medicine services. Local research nurses reviewed medical notes and approached potentially eligible patients. Primary care recruitment reviewed primary care lists from collaborating practices, sending mailshots to patients aged 70 and over who were not taking angiotensin‐converting enzyme inhibitors. Telephone pre‐screening was conducted either by research nurses at each site or centrally by Tayside Clinical Trials Unit. The 10‐point SARC‐F questionnaire was used for pre‐screening. De‐identified recruitment information was held on a central electronic tracking system and analysed using SPSS. Bioimpedance was measured using the Akern BIA 101 system, with the Sergi equation used to estimate lean mass. Results Fourteen UK sites recruited to the trial. The 1202 sets of notes in hospital‐based care were reviewed at these sites; 7 participants (0.6% of total notes screened) were randomized. From primary care, 13 808 invitations were sent; 138 (1.0% of total invited) were randomized. 633/2987 primary care respondents were pre‐screened centrally; the mean number of calls per respondent was 2.3. For 10 sites where central and local pre‐screening could be compared, the conversion rate from pre‐screening to randomization was 18/588 (3.1%) for centralized calls, compared with 73/1814 (4.0%) for local pre‐screening calls (P = 0.29). A weak relationship was seen between higher (worse) SARC‐F score at screening and lower likelihood of progression to randomization (r = −0.08, P = 0.03). Muscle mass estimates generated using the Sergi equation were systematically biased, and a recalibrated equation for bioimpedance‐estimated muscle mass was derived. Conclusions Primary care recruitment led to higher response rates and overall numbers randomized than hospital‐based recruitment. Centralized pre‐screening saved local research nurses' time but did not improve conversion to randomization. SARC‐F did not help to target screening activity in this sarcopenia trial, and a recalibration of the equation for estimating muscle mass from bioimpedance measures may improve accuracy of the screening process.